The Role of International Humanitarian Organizations of the Western Balkans (Serbia Case) - Stajić, Ljubomir; Štrbac, Katarina (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
The Western Balkans in the period from 1992 to 2000 and later was the site of serious armed conflicts in which there was a significant threat to human life and other human rights of the civilian population. The deployment of international humanitarian organizations in this area was significant and with somewhat different role than the example of the African continent or elsewhere. Period of the ten war years as many post-war years of their engagement was quite enough for methodologically correct examenation of their role, problems and attitudes of the "beneficiaries" of these organizations on the activities of these organizations and their synchronization with the government. Numerous problems were noted from the practice of humanitarian organizations that are potencially usefull for improvements in the future. In this paper we present only some parts of the expert group from Serbia extensive research who exactly talking about these problems. Particularly interesting are the data on the abuse of humanitarian aid as well as data that are different from those presented by some official international organizations.